Hong Kong Studies : The Culture and Politics of Realignment - Ki, Magdalen; Liang, Wayne Wen-chun (Hong Kong Culture and Literature, 2025)
This interdisciplinary volume provides a multifaceted exploration of the kaleidoscopic transformation of Hong Kong. It examines the region's diverse historical developments, the challenges of digital surveillance, the impact of Orientalism, the power of individual agency, minor literature, films, popular culture, and the trajectories of creative writing programs. Featuring contributors from various disciplines, including history, literature, and media studies, this volume offers scholarly insights into the dynamic relationships among domestic helpers, immigrants, refugees, and Hongkongers. It presents an essential overview of the complex evolution of Hong Kong as a continually changing Special Administrative Region of China.